Uma abordagem de geomarketing do esporte - Loïc Ravenel (Confins)
This article presents, from a conceptual and functional point of view, the contribution of a geomarketing for the analysis of the sport. Beyond of collusion between geography and marketing, it firstly implies an operational decisional phase for the progression of the sports activity. If its methods borrow much from the space analysis and geomatics, and fall under a structuralist prospect, the interest of the geomarketing should not be limited to the market research, nor to the cartography of the customers or prospective customers within the market radiuses: we wish to go from the mere vision of data representation going towards an integration of geographical dimension into the marketing strategy. This integration leads us towards a more systemic vision, using marketing as a model of analysis of the sporting services, for which the choices of the practitioners or consumers become dominating. After having replaced sports geography research in their scientific context, a definition of geomarketing is proposed, insisting on the specificity of the sporting services. Three great fields of interventions are then identified as of the working tracks which combine expectations of the actors with geographical new prospects.